The Influence of Teachers' Readiness Towards 21stCentury Classroom Management - Jaggil Apak; Muhamad Suhaimi Taat (2018)
This study is aimed at identify the influence of teachers'readiness towards 21stcentury classroom management among secondary school teachers in Sabah, Malaysia. The non-experimental study utilised the survey method by combining several variable sampling techniques to obtain samples. Data was collected through aset of adapted questionnaires administered to 439 teachers. Descriptive analysis shows teachers’ readiness and 21stcentury classroom management being practised at a high level. One-way ANOVA test results show that there is no significant difference in teachers’ readiness and 21stcentury classroom management based on teaching experience. Meanwhile, multiple regression analysis shows that there is a significant influence of teachers' readiness towards 21stcentury classroom management. The findings show that the overall contribution predicted by teachers' readiness towards 21stcentury classroom management is 27.8 percent. Implications and recommendations for further studies are also discussed.